O solo criado em contextos de densificação urbana - Roncato, Janete Teresinha (2015)
The implementations of the value capture mechanism institute as an instrument of urban politics require comprehensive studies about property and the science within the law. It also demands deep understanding of its social and environmental role, the right to build, the planning, the soil ordering, the building activity and the establishment of mechanisms for intervening in the city, among others. From this perspective, this dissertation aims to analyze the cumbersome granting of the right to build as a tool of urban strategies, considering the purposes and municipalities laws to densify urban areas in cities. On the other hand, the role of the property is emphasized as well as its quest for appreciation in the process and the implications upon the quality of life, the traffic, the soil´s use and its occupation. The scope of this paper is the urban environment and the municipal actions to densify areas in conformity to the Statute of the City’s Law 10.257/2001, which stablished this mechanism as a resource for managing the urban environment. In particular, case studies in the city of Curitiba-PR are mentioned, where this institute is applied as a resource to materialize the goals stablished by the City’s Master Plan. The methodology is of qualitative nature and the discussions are based on documents and writings from the press, from the academy and from the interlocutors that present cases of the institute’s implementation. In conclusion, the mechanism of the value capture can operate as a densification factor and bring unexpected results to the city’s inhabitants. However, it attends to what was planned by the municipal executives and the ntrepreneurs who develop the urban space. It was verified that the cumbersome granting of the right to build benefits the real estate capital, compete with the urban plan flexibility and establishes negotiation between the public sector and the involved actors. In Curitiba-PR, in accordance to the case studies, three factors to stimulate the intensive occupation of areas were analyzed. They were: the verticalization, the densification and the heritage conservation. In this sense, the cumbersome granting of the right to build has generated, according to the analyzed examples, the materialization of the urban plan oriented to value even more certain areas of the city that already have infrastructure and convert them into attractive centers of investments.